Java Government Gazette: Koleksi Surat Kabar Berbahasa Inggris Abad Ke-19 Di Perpustakaan Nasional Republik Indonesia - Supratman, Frial Ramadhan (Jurnal Tadwin, 2024)
Thomas Stanford Raffles was one of the governors general who ruled Java between 1811 and 1816. His short period of power is often overlooked by historians. Nevertheless, Raffles' reign played an important role in Indonesian history before independence. The first English language newspaper published during Raffles' reign was the Java Government Gazette. This article investigates and analyzes the Java Government Gazette in the collection of the National Library of the Republic of Indonesia. This newspaper was published between 1812 and 1816. The Java Government Gazette newspaper played a significant role as a source for the history of the Dutch East Indies in the early 19th century. In fact, this newspaper also shows how the Dutch East Indies cannot be separated from the global dynamics of the 19th century. This newspaper provides various information, such as the slave trade, ship transportation, buying and selling of assets and products and information regarding the British and French conflict. This research method is a qualitative method that emphasizes the analysis of historical information in the Java Government Gazette newspaper. In this research, the author argues that the Java Government Gazette newspaper is an important historical source for understanding the position of the Dutch East Indies at the beginning of the 19th century from a global historical perspective.